2006
DOI: 10.1128/iai.00067-06
|View full text |Cite
|
Sign up to set email alerts
|

Adherent and InvasiveEscherichia coliIs Associated with Granulomatous Colitis in Boxer Dogs

Abstract: The mucosa-associated microflora is increasingly considered to play a pivotal role in the pathogenesis of inflammatory bowel disease. This study explored the possibility that an abnormal mucosal flora is involved in the etiopathogenesis of granulomatous colitis of Boxer dogs (GCB). Colonic biopsy samples from affected dogs (n ‫؍‬ 13) and controls (n ‫؍‬ 38) were examined by fluorescent in situ hybridization (FISH) with a eubacterial 16S rRNA probe. Culture, 16S ribosomal DNA sequencing, and histochemistry were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
324
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 232 publications
(341 citation statements)
references
References 86 publications
11
324
1
5
Order By: Relevance
“…However, this is often challenging due to high similarities in the 16S rRNA gene composition among phylogenetically related microorganisms. FISH can also provide important information about the morphology and spatial distribution of microorganisms in the GI tract (Simpson et al 2006).…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…However, this is often challenging due to high similarities in the 16S rRNA gene composition among phylogenetically related microorganisms. FISH can also provide important information about the morphology and spatial distribution of microorganisms in the GI tract (Simpson et al 2006).…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…16S rDNA libraries generated from GCB dogs are dominated by sequences for Enterobacteriaceae, predominantly E. coli and Shigella and FISH probes recognize invasive E. coli within the colonic mucosa (in the lamina propria and macrophages) of Boxer dogs with GCB but not unaffected controls, and non-GCB colitis. E. coli strains isolated from affected Boxer dogs display an AIEC pathotype in cultured cells, and resemble LF82 in phylogeny and virulence genes [45]. Subsequent studies of GCB-affected dogs have shown that antibiotic-induced clinical remission correlates with eradication of invasive E. coli.…”
Section: Aiec Are Associated With Intestinal Inflammation In Dogsmentioning
confidence: 99%
“…In contrast to pathogenic E. coli, such as O157:H7, AIEC strains differ in serotype, overall genotype [26,45] and ribotype [50] and are not a single virulent clone. By use of PCR-based virulence screening and genome subtraction, we discovered that AIEC strains with unique multilocus sequence type sequences and distinct phylogenetic backgrounds (A, B1, B2 and D) harbor chromosomal and episomal elements that are homologous to those described in extraintestinal pathogenic E. coli (uropathogenic E. coli [UPEC] and avian pathogenic E. coli), and pathogenic Enterobacteriaceae, such as Salmonella and Yersinia [26,45], and support the possibility that AIEC strains share common pathoadaptive determinants of virulence.…”
Section: Aiec Strains May Share Common Pathoadaptive Determinants Of mentioning
confidence: 99%
See 2 more Smart Citations